Doulas como "amortecedores afetivos" Notas etnográficas sobre uma nova acompanhante de parto - Soraya Fleischer (Ciências Sociais Unisinos, 2005)
The "doula" is a new character that can be observed in the Brazilian birthing scenario. As in the case of any novelty, many meanings have been gathered to define what a doula is and what is her role during delivery. In this article, I intend to present some recent ethnographic notes designed to provoke reflection (and inspire new research) about the doulas. My argument is that this profession is configuring an ethos that is consistent with the movement for the humanization of delivery and birth, uses dichotomic categories and at the same time maintains a great fluidity between them. In my view, this strategy can sometimes reify a very conventional image of women.